Forest structure and live aboveground biomass variation along an elevational gradient of tropical Atlantic moist forest (Brazil) - Alves, Luciana F.; Vieira, Simone A.; Scaranello, Marcos A.; Camargo, Plinio B.; Santos, Flavio A.M.; Joly, Carlos A.; Martinelli, Luiz A. (Forest ecology and management, 2010)
Live aboveground biomass (AGB) is an important source of uncertainty in the carbon balance from the tropical regions in part due scarcity of reliable estimates of live AGB and its variation across landscapes and forest types. Studies of forest structure and biomass stocks of Neotropical forests are biased toward Amazonian and Central American sites. In particular, standardized estimates of aboveground biomass stocks for the Brazilian Atlantic forest are rarely available. Notwithstanding the role of environmental variables that control the distribution and abundance of biomass in tropical lowland forests has been the subject of considerable research, the effect of short, steep elevational gradients on tropical forest structure and carbon dynamics is not well known. In order to evaluate forest structure and live AGB variation along an elevational gradient (0–1100 m a.s.l.) of coastal Atlantic Forest in SE Brazil, we carried out a standard census of woody stems ≥4.8 cm dbh in 13 1-ha permanent plots established on four different sites in 2006–2007. Live AGB ranged from 166.3 Mg ha −1 (bootstrapped 95% CI: 144.4,187.0) to 283.2 Mg ha −1 (bootstrapped 95% CI: 253.0,325.2) and increased with elevation. We found that local-scale topographic variation associated with elevation influences the distribution of trees >50 cm dbh and total live AGB. Across all elevations, we found more stems (64–75%) with limited crown illumination but the largest proportion of the live AGB (68–85%) was stored in stems with highly illuminated or fully exposed crowns. Topography, disturbance and associated changes in light and nutrient supply probably control biomass distribution along this short but representative elevational gradient. Our findings also showed that intact Atlantic forest sites stored substantial amounts of carbon aboveground. The live tree AGB of the stands was found to be lower than Central Amazonian forests, but within the range of Neotropical forests, in particular when compared to Central American forests. Our comparative data suggests that differences in live tree AGB among Neotropical forests are probably related to the heterogeneous distribution of large and medium-sized diameter trees within forests and how the live biomass is partitioned among those size classes, in accordance with general trends found by previous studies. In addition, the elevational variation in live AGB stocks suggests a large spatial variability over coastal Atlantic forests in Brazil, clearly indicating that it is important to consider regional differences in biomass stocks for evaluating the role of this threatened tropical biome in the global carbon cycle.